Colonic mucinous adenocarcinoma in a tufted deer: differential diagnosis and literature review. (November 2022) - Gonzalez-Astudillo, Viviana; Navarro, Mauricio A.; Moore, Janet; Uzal, Francisco A.
An 18-y-old female tufted deer ( Elaphodus cephalophus ) had a short history of chronic diarrhea, progressive weight loss, and hindlimb instability. Given the poor prognosis, the deer was euthanized and submitted for postmortem examination. The most significant gross finding was segmental and multinodular mural thickening of the proximal colon. On cut surface of the affected colonic segments, 0.5–2-cm diameter, intramural, multiloculated, cystic structures containing gray, translucent, gelatinous material elevated the edematous mucosa. Microscopically, the intramural cystic structures were filled with mucinous matrix admixed with foamy macrophages, and lined by discontinuous segments of well-differentiated columnar, pancytokeratin-positive epithelium with basilar nuclei. Multifocally, transition was observed from hyperplastic mucosal crypt epithelium to dysplastic or neoplastic columnar and flattened epithelium lining submucosal and serosal cysts. Cyst lumina were irregularly disrupted by polypoid ingrowths of collagenous tissue covered by attenuated epithelium. Based on these findings, we diagnosed a well-differentiated mucinous adenocarcinoma. Although intestinal adenocarcinomas have been described in humans and animals, they are considered uncommon in most domestic species, except for sheep, for which genetic and environmental factors appear to influence occurrence. Our report addresses the knowledge gap regarding intestinal adenocarcinomas affecting cervids and specifically the tufted deer, a less-studied, near-threatened Asian cervid.